Artikulasi Fikih Kesehatan dalam Kebijakan Kesehatan Global: Pendekatan Integratif antara Maqāṣid al‑Syāriʿah dan Ilmu Kesehatan - Azami, Canda Ulul; Fara, Syarifah Aisyah; Hafidz, Raihan Alwan; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2025)
The discipline of health jurisprudence (fiqh al-ṣihhah) represents an emerging interdisciplinary field that aims to harmonize Islamic legal principles with contemporary health sciences. This integration is increasingly relevant as modern societies face complex public health challenges that intersect with ethical, cultural, and religious dimensions. Islam, through its emphasis on the preservation of life (ḥifẓ al-nafs), cleanliness, and community welfare, provides a strong moral framework for addressing health issues. However, many public health policies, both at national and global levels, often neglect these Islamic ethical foundations. As a result, certain interventions—such as vaccination programs, pandemic control measures, or social restrictions—encounter resistance from communities that perceive them as incompatible with their faith-based values.This study seeks to bridge that gap by proposing an articulation model between maqāṣid al-syāriʿah (objectives of Islamic law) and modern public health science. The approach emphasizes the principle of ḥifẓ al-nafs as the core of Islamic concern for human well-being and encourages value-based ijtihād to reinterpret health-related rulings in contemporary contexts. The research employs a library-based methodology, analyzing policy documents, pandemic response strategies, and current literature on Islamic jurisprudence and bioethics.The findings suggest that incorporating health jurisprudence within public health frameworks can enhance the moral legitimacy and societal acceptance of health policies. Furthermore, it fosters better compliance with medical recommendations and reduces conflicts between scientific imperatives and religious beliefs. In conclusion, developing a maqāṣid-oriented policy framework that is adaptable to both local and global contexts is essential. Establishing institutional platforms for continuous dialogue between Islamic scholars and health professionals, alongside promoting health-fiqh literacy, will strengthen the ethical foundation and public understanding of contemporary health governance.